On an integral equation - Lowndes, J. S. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The object of this paper is to obtain the solution of a general class of integral equations examples of which occur widely in boundary value problems in applied mathematics. In particular the solution of a generalization of an integral equation which arises in certain electrostatic problems is presented and shown to include as a special case an equation whose solution has been given by Kalla.